Spatio-temporal study on coupling coordination between urbanization and eco-resilience in the Erhai Lake Basin - Zhanting Deng; Yuhan Chen; Fengshan Jiang; Yangbin Zhang; Zhiqiang Xie; Yuning Zhang; Lei Zhao (All Earth)
Amidst the rapid urbanisation, the ecological environment of plateau lake basins faces significant challenges. To better coordinate the relationship between urbanisation development and ecological environment construction, this paper conducts an analysis and assessment of the ecological resilience and urbanisation coupling coordination in Dali Prefecture based on socio-geographical spatial data. Initially, an assessment model for ecological resilience is established using resilience theory. Subsequently, the urbanisation development level is evaluated based on panel data. Finally, a coupling coordination model is employed to calculate the coupling coordination between the two aspects. The results indicate: (1) a rapid increase in basin urbanisation from 2010 to 2019, particularly between 2010 and 2015; (2) a continuous expansion of low-value ecological resilience areas across the entire basin, with a predominance of townships experiencing fluctuating decreases or stagnation, leading to an overall negative trend in ecological resilience indices; (3) evident spatial and temporal disparities in coupling coordination between the two systems in the basin’s villages and towns, primarily reflected in differences in coupling coordination types, with a few towns consistently exhibiting environmental lag. This study introduces a customised ecological resilience model for the Erhai Basin, enhancing comprehension of urbanisation-ecological resilience dynamics in plateau lake basins.